2023
DOI: 10.1177/13591053231189419
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 prevention burnout impacts emotional symptoms among Chinese college students: A moderated mediation model

Abstract: The current study investigated the relationship between COVID-19 prevention burnout and emotional symptoms (depression and anxiety) among 1,837 Chinese college students and the underlying mechanisms. Results from moderated mediation analysis revealed that the association between COVID-19 prevention burnout and emotional symptoms was mediated by psychological inflexibility (β = 0.20, 95%CI = [0.10, 0.19]). Also, COVID-19 prevention burnout’s direct and indirect effects on emotional symptoms were more substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The external environment has a significant impact on burnout. The researchers found that fear of COVID-19 and coronavirus stress significantly positively predicted COVID-19 burnout (Chen et al, 2023;Yıldırım and Ashraf, 2023;Yıldırım et al, 2023a).This is consistent with our research findings. Our results indicate that both school climate and psychological capital significantly negatively predict academic burnout.…”
Section: The Relationship Among School Climate Psychological Capital ...supporting
confidence: 91%
“…The external environment has a significant impact on burnout. The researchers found that fear of COVID-19 and coronavirus stress significantly positively predicted COVID-19 burnout (Chen et al, 2023;Yıldırım and Ashraf, 2023;Yıldırım et al, 2023a).This is consistent with our research findings. Our results indicate that both school climate and psychological capital significantly negatively predict academic burnout.…”
Section: The Relationship Among School Climate Psychological Capital ...supporting
confidence: 91%
“…Student burnout is a complicated phenomenon that can result from various academic and personal factors (Chen et al, 2023). The burnout may be attributable to the adverse emotional climate characterized by high levels of stress, anxiety and conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression are the most common psychological problems that can easily lead to job burnout, as evidenced by many literatures ( 5 , 33 , 34 ). In addition, burnout is affected by many other factors such as psychological resilience ( 35 , 36 ), fear ( 37 , 38 ), and psychological inflexibility ( 39 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%